2001
DOI: 10.3758/bf03196390
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on reality-monitoring decisions

Abstract: A modified Asch (1951) conformity paradigm was used to study the impact of social influence on reality-monitoring decisions about new items. Subjects studied pictures of some objects and imagined others. In a later test phase, they judged whether items had been perceived in the study phase, had been imagined, or were new. Critically, for some items, the subjects were informed of a confederate's response before rendering a judgment. Although the confederate was always correct when they responded to old items, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 38 publications
8
52
1
1
Order By: Relevance
“…Os paradigmas de conformidade usam tipicamente métodos que envolvem informações falsas inseridas em questionários de recordação (Hoffman, Granhag, Kwong See, & Loftus, 2001) ou em que o experimentador revela respostas de outras testemunhas fictícias, mas sempre sem a possibilidade do participante discutir tais informações com outras testemunhas (Luus & Wells, 1994). Novos estudos optaram por delineamentos com maior validade ecológica, com interações ao vivo de testemunhas oculares, por meio do uso de cenários mais realísticos (Roediger, Meade, & Bergman, 2001 O uso de confederados, também, é um procedimento regular em muitos estudos sobre conformidade e influência social.…”
Section: Influência Social E Conformidade No Relato De Testemunhasunclassified
“…Os paradigmas de conformidade usam tipicamente métodos que envolvem informações falsas inseridas em questionários de recordação (Hoffman, Granhag, Kwong See, & Loftus, 2001) ou em que o experimentador revela respostas de outras testemunhas fictícias, mas sempre sem a possibilidade do participante discutir tais informações com outras testemunhas (Luus & Wells, 1994). Novos estudos optaram por delineamentos com maior validade ecológica, com interações ao vivo de testemunhas oculares, por meio do uso de cenários mais realísticos (Roediger, Meade, & Bergman, 2001 O uso de confederados, também, é um procedimento regular em muitos estudos sobre conformidade e influência social.…”
Section: Influência Social E Conformidade No Relato De Testemunhasunclassified
“…A host of studies have examined these social conformity effects on a variety of judgments (e.g., Baron, Vandello, & Brunsman, 1996;Hoffman, Granhag, Kwong See, & Loftus, 2001), and a growing number of studies have examined these effects on explicit recognition judgments (Allan & Gabbert, 2008;Axmacher, Gossen, Elger, & Fell, 2010;Gabbert, Memon, & Wright, 2007;Meade & Roediger, 2002;Reysen, 2005;Schneider & Watkins, 1996;Walther, Bless, Strack, Rackstraw, Wagner, and Werth 2002;Wright, Gabbert, Memon, & London, 2008;Wright, Self, & Justice, 2000). In general, the findings have shown that participants will shift their recognition memory decisions toward confederates' even when those confederates' reports are incorrect, a phenomenon termed "memory conformity."…”
mentioning
confidence: 92%
“…A number of recent articles have examined the impact of working with others on participants' memory performance (see, e.g., Basden, Reysen, & Basden, 2002;Betz, Skowronski, & Ostrom, 1996;Bless, Strack, & Walther, 2001;Gabbert, Memon, & Wright, 2006;Hoffman, Granhag, See, & Loftus, 2001;Meade & Roediger, 2002). Some of these studies have found that adding a social context to more traditional memory paradigms can lead to different results than those obtained using methods in which participants are asked to remember information on their own (e.g., Reysen, 2007).…”
mentioning
confidence: 99%